WAKAF PRODUKTIF SEBAGAI INSTRUMEN PENGEMBANGAN INDUSTRI MAKANAN HALAL DI INDONESIA - Ardiansyah Saputra (Program Studi Manajemen Dakwah - Fakultas Dakwah dan Ilmu Komunikasi - UIN Syarif Hidayatullah Jakarta, 2020)
The purpose of this research is to find out how productive waqf is as an instrument for developing halal food and to find out the supporting and inhibiting factors. The method used in this research is descriptive qualitative with a literature review of the relevant theories. The data used is secondary data obtained from sources either journals or statistical data taken from the Central Statistics Agency, the Ministry of Cooperatives and SMEs, and Thomson Reuters.The results of the study explain that the halal food industry will get support from two sides, the first is from the financing provided to MSMEs that have not been certified halal and from the distribution of maukuf funds alaih the results from investments channeled from waqf funds. If the scheme is implemented massively and on a large scale, it will grow the number of MSMEs that have halal certification, which in aggregate will also grow the number of the halal food industry in Indonesia. Keywords: Waqf; Productive; Halal Food